(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article deals with the actual problem of expanding intercultural communicative competence in the educational process. Since the key role in this process belongs to higher education, this phenomenon is considered in English lessons. The purpose of the article is to highlight the stages of development of intercultural competence of students of non-linguistic higher education, thus higher education involves a complex process of development of cognitive, social, emotional and cultural characteristics of the personality of future specialists. Modern process of international integration necessitates the search for new approaches to professional training of specialists, the main part of which is teaching foreign languages using innovative methods and technologies. The article presents the main approaches and principles of the formation of intercultural communicative competence in the process of teaching a foreign language to students. As a result of the rapid development of intercultural communication and global transformations taking place in the world since the late 90s of the twentieth century, there is a need to create a personality with a new set of qualities and competencies that are urgently needed for rational functioning in a multicultural world.